Meta de inflação e contratos para bancos centrais (Economia Aplicada, 1998)
Inflation targeting is a framework for monetary policy, that has recently been implemented in some developed nations. In this article, it is shown that one can interpret inflation targeting cum penalties as equivalent to the optimal linear contract. Moreover, the conditions for the successful implementation of inflation targeting are discussed, based on these countries' experience. A monetary reform based on inflation targeting may be an important step towards the consolidation of an economic stabilization plan.